Pengaruh Motivasi, Disiplin, Dan Kerjasama Terhadap Kinerja Karyawan PT Sarana Panen Perkasa Medan - Sinto, Sinto; Dewi, Sri Puspa; Chomariah, Siti (Jurnal Prodi Fakultas Ekonomi-UISU, 2024)
This research was conducted with the aim of determining the influence of Motivation, Discipline and Cooperation on the Performance of PT Sarana Panen Perkasa Medan Employees. This research uses quantitative research methods with primary and secondary data sources using a Likert scale. The total sample of research respondents was 108 respondents. This data processing uses SPSS Version 25. Based on the results of the partial test, the results obtained are that the Motivation variable has no effect on Employee Performance, seen from the t value 1.081 t table 1,659, with a significance level of 0.282 0.05. Then the Discipline variable also has an influence and is significant on employee performance, seen from the tcount value of 5.492 1.659, with a significance level of 0.0000.05. And the Collaboration variable has a significant influence on Employee Performance, seen from the tcount value of 7.319 ttable 1.659, with a significance level of 0.000 0.05. In the simultaneous test, this result shows that F countF table, namely 54,7972.46 with a significance level of 0.000 0.05. So, it can be concluded that the variables Motivation (X1), Discipline (X2) and Cooperation (X3) together have a positive and significant effect on employee performance at PT Sarana Panen Perkasa.